Investigation of the effects of intranasal desmopressin on the bleeding of the patients during open septorhinoplasty: A randomized double-blind clinical trial - Maliheh Akbarpour; Mir-Mohammad Jalali; Maryam Akbari; Sevil Nasirmohtaram; Soudabeh Haddadi; Ali Faghih Habibi; Fateme Azad (Heliyon, 2023)
Objectives: Rhinoplasty is one of the most common cosmetic surgeries in the world. Lack of adequate local homeostasis may lead to excessive bleeding during the operation, which increases the time of operation and recovery period, and the prevalence of complications. This study investigated the effects of nasal desmopressin on the quality of the surgical field and the volume of bleeding during rhinoplasty. Materials and methods: This double-blind randomized clinical trial was performed on 120 patients aged 18–40 years who were candidates for rhinoplasty. Patients were randomly divided into three groups: low-dose desmopressin group and high-dose desmopressin group and placebo group. Hemodynamic changes and surgical field based on BOEZAART criteria, and the volume of bleeding were calculated. Results: In this study 115 women (95.8%) and 5 men (4.2%) participated. The mean age of patients was (27 ± 6.8). Bleeding volume in high dose desmopressin group was (21.7 cc ± 12.3), (27.7 cc ± 12.3) in low dose group, and (38.3 cc ± 12.3) in the placebo group, The difference in blood volume among the three groups was statistically significant with p < 0.005. Clean surgical field according to BOEZAART classification was marginally significant in both desmopressin groups. The differences in blood pressure, heart rate, blood and urine sodium, and hemoglobin before and after surgery between groups there not statistically significant. Conclusion: Based on the results of the present study topical nasal spray desmopressin can reduce surgical field bleeding during rhinoplasty. To generalize the results to other surgeries in the ENT field it is recommended to conduct studies.